2015
DOI: 10.1096/fj.14-258236
|View full text |Cite
|
Sign up to set email alerts
|

Scleraxis is required for the development of a functional tendon enthesis

Abstract: The attachment of dissimilar materials is a major engineering challenge, yet this challenge is seemingly overcome in biology. This study aimed to determine how the transcription factor Scleraxis (Scx) influences the development and maturation of the tendon-to-bone attachment (enthesis ] littermates were killed at postnatal days 7-56 (P7-P56). Enthesis morphometry, histology, and collagen alignment were investigated throughout postnatal growth. Enthesis tensile mechanical properties were also assessed. Laser mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
74
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 47 publications
0
74
0
Order By: Relevance
“…As discussed earlier, deletion of Scx results in loss of bone eminences, but the basic ability of tendon to attach to skeleton is not impaired. At postnatal stages however, organization and mineralization of the enthesis is subsequently disrupted in Scx mutants (Killian and Thomopoulos, 2016). It is still not completely clear whether these defects are due directly to Scx function in enthesis cells, since tendons are also drastically impaired in Scx mutants and postnatal pups show limited mobility, which could therefore affect mechanical loading of the enthesis.…”
Section: Enthesesmentioning
confidence: 99%
“…As discussed earlier, deletion of Scx results in loss of bone eminences, but the basic ability of tendon to attach to skeleton is not impaired. At postnatal stages however, organization and mineralization of the enthesis is subsequently disrupted in Scx mutants (Killian and Thomopoulos, 2016). It is still not completely clear whether these defects are due directly to Scx function in enthesis cells, since tendons are also drastically impaired in Scx mutants and postnatal pups show limited mobility, which could therefore affect mechanical loading of the enthesis.…”
Section: Enthesesmentioning
confidence: 99%
“…Because it has been reported that the forces applied by muscles and tendons to the enthesis are important for bone ridge formation, we investigated the effects of mechanical unloading using tendon‐severing operation or hindlimb unloading in tail‐suspended mice. We found that bone eminences in Anxa5 –/– mice were reduced to levels comparable to those in Anxa5 +/+ mice by 8 weeks after tenotomy or hindlimb unloading, suggesting that bone eminence formation in response to mechanical tension is restricted by expression of Anxa5.…”
Section: Discussionmentioning
confidence: 99%
“…Prx1Cre mice (strain 005584) were purchased from The Jackson Laboratory. The genotypes of mice were determined from toe and tail biopsies by using PCR-based analysis of DNA for Cre, Scx-null, Scx-WT, and Scx-flox alleles (13,22). Scx-mutant mice were developed by using Scx flx/flx mice crossed with Prx1-Cre; Scx flx/WT mice.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Although dispensable in small animal models of long bone fracture healing (12), the role of BMP-4 in long bone development is evident. Recent work has shed light on the development of bone ridges in long bones, specifically at the interface between tendon and bone (13)(14)(15)(16)(17)(18)(19)(20). The shape and formation of bone ridges on skeletal elements is regulated, first, by specification of progenitors by TGF-b, followed by differentiation mediated by BMP-4 and scleraxis (Scx), a tendon progenitor marker (15,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation